Upaya Pemerataan Pembangunan Desa Di Wilayah Perbatasan Indonesia - Asep Syarifuddin Hidayat (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
As an equitable form of village development, the government must also pay attention to village development in border areas, which is often neglected by the government. The purpose of this study is to understand the distribution of rural funds in frontier areas. The method used is a qualitative research approach with an empirical approach. Data collection techniques were conducted through interviews. The findings show that villages become stronger after the government distributes them as